Achieving burst Li+ channels via quasi-two-dimensional fluorinated metal-organic framework modulating functionalized interface - Lingchen Kong; Yu Li; Cong Peng; Ziyue Zhao; Junwei Xiao; Yimin Zhao; Wei Feng (Nature Communications)
Abstract The development of disordered Li dendrite and the adverse reaction between Li and electrolyte impede practical use of Li metal batteries (LMB). Herein, we propose quasi-two-dimensional fluorinated metal-organic framework carbon (q2D-FcMOF) that is utilized to construct artificial solid electrolyte interface (ASEI) to achieve robust interfacial protective double-layer. The outer organic layer provides ample space for Li deposition, while the inner inorganic LiF layer promotes conduction of Li+ and blocks electron transport. Metal clusters within the hybrid layer are uniformly dispersed, encouraging Li+ to cluster around metal active sites that are thermodynamically compatible with Li. Consequently, q2D-FcZ8@Li symmetrical batteries demonstrate an ultralong cycle life over 3600 h. When paried with commercial cathodes, the cells exhibite cyclability under conditions of high-loading, lean-electrolyte, even exposure to air for some time. This research suggests an effective method for fabricating ASEI using 2D quasi-ordered superstructure MOF NPs, which is expected to the development of LMB.